DETEKSI PERUBAHAN RUANG TERBUKA HIJAU PADA 5 KOTA BESAR DI PULAU JAWA (Studi kasus : DKI JAKARTA, KOTA BANDUNG, KOTA SEMARANG, KOTA JOGJAKARTA, DAN KOTA SURABAYA) - Ariev Budiman; Bambang Sulistyantara; Alinda FM Zain (http://arl.faperta.ipb.ac.id/, 2014)
Some major cities in Java Island such as DKI Jakarta, Bandung, Semarang, Yogyakarta and Surabaya showed rapid growth. It was mainly due to fast economic and population growth. In those cities, it was reported that the economic and population growth are around 6-7% and 1.5 – 2.5% respectively. The economic and population growth will increase the need of land for development of economic centers and residences. This situation will cause land use change especially in greenery open space. The objective of this study is to detect the change of greenery open space in five major cities in Java Island: DKI Jakarta, Bandung City, Semarang City, Yogyakarta City, and Surabaya City.This study found that greenery open space in DKI Jakarta decreased by 57.5% within a period of 31 years from 1982 to 2013 or about 1.8% / year. In Bandung City greenery open space decreased by 42% within a period of 22 years from 1991 to 2013 or about 2% / year. Greenery open space in Yogyakarta also decreased. Within a period of 41 years from 1972 to 2013 there was a decrease of 28% or 1.5% / year. Different situation was found in Semarang City and Surabaya City. In Semarang City, there was an increase of 62% of greenery open space within a period of 13 years from 2000 to 2013 or 4.7% / year. While in Surabaya City, greenery open space increased by 116% within a period of 13 years from 2000 to 2013 or 8.9% / year.